Cancer Pain Management at a Specialist Palliative Care Inpatient Unit: An Audit - Dalton, Sadhbh; Jones, Cormac; Power, Robert; McMahon, Des; Barrett, Michelle; Dhuibhir, Pauline; Walsh, Declan (Trinity Student Medical Journal, 2018)
Cancer pain is prevalent and burdensome in a palliative care setting and managed pharmacological and through non-pharmacological means. There is variance in how effectively cancer pain is managed, and to address this the ‘Pharmacological Management of Cancer Pain in Adults’ was published by the Department of Health in November 2015. To assess adherence to the standards defined by the ‘Pharmacological management of Cancer Pain in Adults’. Our study audited the implementation of these guidelines regarding recording pain, administering analgesics, dealing with side effects and opioid toxicity. Three researchers reviewed the charts of 100 consecutive cancer admissions between 01/09/17 and 31/12/17 in a Dublin hospice. This Information was used to assess adherence to 15 audit standards. Of the 15 audit standards examined, 9 met this goal of 100% compliance. 3 of the remaining 6 standards had a compliance equal or greater than 90%. There is a high degree of compliance in the assessment and management of cancer pain. Where compliance is not 100% clinical practice should be reviewed or feedback given on the audit tool. Future research should focus on completing the audit cycle, and further audit in a community or acute hospital setting.